A post Montecristi review on the nature of indigenous justice and its treatment in Ecuador - Bajaña-Tovar, Fernando Stalin (2019)
The nature of indigenous justice has generally been shown to be well known in the context of the Ecuadorian legal culture, with political approaches predominating that identify it indiscriminately between different categories that are not always compatible. The absence of a theoretical foundation that has emanated exclusively from the legal sciences has allowed the proliferation and elevation of reductionist beliefs within the Ecuadorian society, in such a way that the whimsical interpretations, that observe in the institution in examine, are not strange. Pre-Columbian punitive havoc and an opera marked by cold water and nettle. The present essay intends to reexamine the main theses that have been advanced about the nature of indigenous justice, in order to demonstrate the weaknesses that are evident at the time of its application. In addition to the negative implications that have been demonstrated by their adoption by the Ecuadorian legal texts.